2015
DOI: 10.2337/dc15-1765
|View full text |Cite
|
Sign up to set email alerts
|

Altered Peripheral B-Lymphocyte Subsets in Type 1 Diabetes and Latent Autoimmune Diabetes in Adults

Abstract: OBJECTIVEB lymphocytes play an important role in the immunopathogenesis of autoimmune diabetes. We hypothesized that the altered B-cell subset phenotype is associated with autoimmune diabetes.RESEARCH DESIGN AND METHODSPatients with type 1 diabetes (T1D) (n = 81), latent autoimmune diabetes in adults (LADA) (n = 82), or type 2 diabetes (T2D) (n = 95) and healthy control subjects (n = 218) with normal glucose tolerance (NGT) were recruited. We determined the percentage of circulating B-lymphocyte subsets, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 40 publications
8
69
1
2
Order By: Relevance
“…Furthermore, our finding that T1D subjects harbor significantly fewer IL-10 pos CD5 + B cells than Ab + subjects (Figure 4) confirms and offers plausible explanation for the recent observations by Kleffel et al (34) and Deng et al (35) of decreased frequency of IL-10 pos Breg cells in T1D. We speculate that FasL + CD5 + B cells could be involved in the deletion of IL-10 pos CD5 + B cells.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our finding that T1D subjects harbor significantly fewer IL-10 pos CD5 + B cells than Ab + subjects (Figure 4) confirms and offers plausible explanation for the recent observations by Kleffel et al (34) and Deng et al (35) of decreased frequency of IL-10 pos Breg cells in T1D. We speculate that FasL + CD5 + B cells could be involved in the deletion of IL-10 pos CD5 + B cells.…”
Section: Discussionsupporting
confidence: 89%
“…Cell acquisition was performed by using a BD Canto II system and analyzed with FlowJo software as described previously [28]. In brief, total B cells were gated in a SSC/CD19 dot plot.…”
Section: Methodsmentioning
confidence: 99%
“…Deng and colleagues used fresh blood [18] and larger patient cohorts to study circulating B lymphocyte subsets. They found that T1D patients had decreased percentages of B10 B cells (which they defined as CD19+CD5+CD1d hi ) and follicular B cells (CD19+, CD23+, CD21−), and an increased percentage of marginal zone-like B cells (CD19+, CD21+, CD23−) compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…In some patient groups, an increased frequency of CD5+ B cells is observed, but is unclear if the CD5+ B cells represent an autoimmune-prone B1-like population or enhanced production of early-stage B cells, as frequencies of CD5+ transitional cells are elevated in early childhood [21]. Other studies either failed to show differences between T1D subjects and controls, or showed differences, using limited subsetting schema [16, 18]. Despite their technical limitations, the preceding data point to potential correlations between T1D and alterations in the peripheral B cell compartment.…”
Section: Introductionmentioning
confidence: 99%